Collaborative Educational Study on Traditional Medicine and Biodiversity Conservation within UNESCO Biosphere Reserve - Mammadova, Aida; Payyappallimana, Unnikrishnan; Chethala N, Vishnuprasad; Badiger, Shrinivas (European Journal of Sustainable Development, 2024)
We investigated the potential synergies between Ayurveda and Kampo within the context of biodiversity conservation in Mt. Hakusan Biosphere Reserve, to elucidate the linkages between traditional medicinal practices and conservation efforts. Methodology: 20 Indian students with backgrounds in Ayurveda and Nature Conservation from The University of Trans-Disciplinary Health Sciences and Technology (TDU) participated in an educational program at Mt. Hakusan Biosphere Reserve in Japan, facilitated by Kanazawa University. The program included lectures, fieldwork, and interactive sessions comparing Ayurveda with Kampo to explore connections with biodiversity conservation. Data were collected through pre- and post-program surveys to assess participants' awareness levels and perceptions, alongside qualitative methods such as participant observations. Results: Findings indicate a significant increase in awareness about UNESCO Biosphere Reserves among participants following the educational intervention. Students perceived the program positively and expressed interest in further research within Biosphere Reserves. However, some respondents reported only marginal increases in awareness, suggesting potential areas for program improvement. Conclusions: The study underscores the potential for cross-cultural collaboration in advancing traditional medicine and biodiversity conservation. Positive participant responses highlight the efficacy of educational programs in fostering awareness and interest in sustainable healthcare practices, with implications for future research and educational initiatives. Keywords: Ayurveda, Kampo, Traditional Medicine, Biodiversity Conservation, Biosphere Reserve, Cross-cultural collaboration